OPTIMASI PRODUK COOLER BOX BERBASIS TERMOELEKTRIK UNTUK MEDIA PENYIMPANAN OBAT - Achmad Gilang Perkasa, (2021)
Medicine is a very important component for human health, therefore the quality of a drug must also be maintained in order to avoid physical and chemical damage and also its quality is maintained. This is because drug storage is an important factor in maintaining drug quality because if the quality decreases, the yield of the drug will also decrease. In this paper, the authors take steps to optimize the storage area for drugs that are not in accordance with the provisions or have not been optimal from the previously made drug storage. The purpose of this paper is to produce a drug storage area that can produce and maintain low temperatures and is environmentally friendly. This medicine storage area is made using Styrofoam as a storage container with iron as a frame to make it stronger. Coupled with a thermoelectric module attached to the top of Styrofoam which functions to produce low temperatures in the drug storage area. This drug storage area has dimensions of 275 x 280 x 480 mm, and has an estimated price of Rp. 749,000